Nanosilver Biocidal Properties and Their Application in Disinfection of Hatchers in Poultry Processing Plants - Marcin Banach; Leszek Tymczyna; Anna Chmielowiec-Korzeniowska; Jolanta Pulit-Prociak (Bioinorganic Chemistry and Applications)
The aim of this study was to use aqueous suspensions of silver nanoparticles with a wide spectrum of particle sizes, variable morphology, high stability, and appropriate physicochemical properties to examine their bactericidal and fungicidal properties against microorganisms present in poultry processing plants. At the same time, the particles were tested for preventing the production of odorogenous pollutants during incubation and thereby reducing the emission of harmful gases from such types of facilities. The results show that the use of nanosilver preparations in order to disinfect eggs and hatchers reduced microbiological contamination. The bactericidal and fungicidal efficacy of the applied preparation was comparable to UV radiation and its effectiveness increasing during the incubation. Good results were achieved in terms of the level of organic gaseous contaminants, which decreased by 86% after the application of the nanosilver preparation.